Approaches to understanding protein hypersecretion in fungi. Issue 4 (October 2016) - Reilly, Morgann C.; Magnuson, Jon K.; Baker, Scott E.
Abstract: Fungi are well known for secreting high levels of proteins. A number of strategies have been used to characterize and maximize protein secretion for industrial purposes. In this review, we highlight three different ascomycetes and focus on a specific protein production example for each. Aspergillus niger has been utilized as a production host for amylases and multiple molecular genetic approaches have been applied to increase secretion in this organism. Saccharification of plant biomass is an integral part of biofuel production and classical genetic and genomic approaches have been used in Trichoderma reesei to understand and manipulate the pathways controlling secretion of plant cell wall degrading enzymes. Finally, Neurospora crassa, a model filamentous ascomycete has been exploited to understand a wide range of biological processes including protein secretion.